Chocolates containing encapsulated in cocoa butter microemulsion cells of a probiotic strain Lactiplantibacillus plantarum - Dobrev Iliyan; Goranov Bogdan; Hadjikinova Raina; Denkova Zapryana; Ivanova Petya (BIO Web of Conferences)
Chocolates were prepared with the probiotic strain Lactiplantibacillus plantarum 13/20 and a prebiotic component of blackcurrant, cherry and blueberry flours. The probiotic cells were introduced by encapsulation in cocoa butter and the prebiotic components by dissolution in an alginate gel. The rheological performances of the resulting chocolates were investigated. It was shown that the addition of prebiotic in the amount of 3.5% negatively affected the rheological properties as well as the organoleptic performance. The candies were characterized by higher moisture content. It has been shown that the size of the gel beads significantly affected the rheology of the chocolate products. The larger the diameter of the gel beads, the stronger their influence on the rheological properties of the chocolates. The sample with gel pearls and blueberry at 2,5% had the best organoleptic characteristics. The microbiological status of the chocolates was determined. All chocolates met the standard requirements for microbiological safety.